Yin-Yang Theory In Chinese Philosophy and its Contribution to the Implementation of Gender Equality in Vietnam: Yin-yang theory in chinese philosophy and its contribution to the implementation of gender equality in vietnam - Văn Dũng, Võ (Fragmentos de Filosofía, 2024)
The Yin – Yang theory in Chinese philosophy is an important component of traditional Chinese culture which has an impact on society by promoting gender equality. It not only emphasizes balance between opposing elements such as men and women, but also encourages respect and appreciation for the roles of both genders in society. In this article, the author will focus on clarifying the content and basic principles of Yin – Yang theory in Chinese philosophy from the perspective of gender equality; the influence of Yin - Yang theory on the implementation of gender equality in Vietnam; contribution of Yin - Yang theory to the implementation of gender equality in Vietnam. Finally, the author made comments and proposed future research directions.